2021
DOI: 10.26911/thejhpb.2021.06.02.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Uptake of COVID-19 Preventive Measures among Persons Aged 13-80 Years during Lockdown in Wakiso, Uganda: A Cross-Sectional Study

Abstract: Background: Health infodemic undermines public health response, results in poor observance of public health measures and costs lives. Health campaigns will not produce intended results without controlling misinformation. This study aimed to analyzed the correlation between infodemic, COVID-19 stress and media trust. Subjects and Method: This was a cross sectional study conducted using online structured questionnaire, from December 2020 to January 2021. A total of 470 participants among African twitter communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…APHS is an open urban population-based cohort which enrolls about 5,000 consenting adults aged 13–80 years in the three communities of Wakiso, central Uganda and these communities include; Kazo, Lukwanga and Sentema. The AMBSO-PHS aims have been previously described through the APHS cohort profile [ 4 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…APHS is an open urban population-based cohort which enrolls about 5,000 consenting adults aged 13–80 years in the three communities of Wakiso, central Uganda and these communities include; Kazo, Lukwanga and Sentema. The AMBSO-PHS aims have been previously described through the APHS cohort profile [ 4 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study used APHS data for round three (R3). The APHS sampling procedure has been previously described [ 4 , 29 ] and this was also similar to other Population based surveys conducted elsewhere [ 30 ]. In brief, multistage sampling was employed to select the different communities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The information was obtained through the tobacco smoking modules of the semi-structured questionnaire administered as part of the AMBSO-PHS. The APHS aims have been previously described [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The control of the disease is still through preventive measures including but not limited to hand hygiene (frequent hand washing and sanitization) keeping social distance, use of face masks and vaccination. Except vaccination, a population based Ugandan study reported a higher uptake of COVID-19 preventive measures (2).…”
Section: Introductionmentioning
confidence: 99%